2022
DOI: 10.1103/physrevd.105.064066
|View full text |Cite
|
Sign up to set email alerts
|

On-shell equivalence of general relativity and Holst theories with nonmetricity, torsion, and boundaries

Abstract: We study a generalization of the Holst action where we admit nonmetricity and torsion in manifolds with timelike boundaries (both in the metric and tetrad formalism). We prove that its space of solutions is equal to the one of the Palatini action. Therefore, we conclude that the metric sector is in fact identical to general relativity (GR), which is defined by the Einstein-Hilbert action. We further prove that, despite defining the same space of solutions, the Palatini and (the generalized) Holst Lagrangians a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…While Witten et al have found canonical and covariant formulations with symplectic structure, no Hamiltonian density was found [28][29][30][31][32]. Researchers have recently explored Witten's use of covariant, canonical, and symplectic structures in a wide range of gravitational theories, often referred to as covariant phase space methods [39][40][41][42]. DDW theory contains poly symplectic/multisymplectic geometry, which contains a Hamiltonian density and a conjugate poly momentum field.…”
Section: Appendix B Poly Koopman-von Neumann Mechanics As De Donder-w...mentioning
confidence: 99%
See 1 more Smart Citation
“…While Witten et al have found canonical and covariant formulations with symplectic structure, no Hamiltonian density was found [28][29][30][31][32]. Researchers have recently explored Witten's use of covariant, canonical, and symplectic structures in a wide range of gravitational theories, often referred to as covariant phase space methods [39][40][41][42]. DDW theory contains poly symplectic/multisymplectic geometry, which contains a Hamiltonian density and a conjugate poly momentum field.…”
Section: Appendix B Poly Koopman-von Neumann Mechanics As De Donder-w...mentioning
confidence: 99%
“…Ashtekar found a symplectic Hamiltonian density that used a hypersurface based on null infinity, but this was restricted to the study of general relativity [38]. Covariant phase space methods have been recently explored in a wide class of gravitational theories [39][40][41][42]. However, a comprehensive formulation of arbitrary field theory with a covariant, symplectic, and canonical Hamiltonian density still appears to be lacking to the best of our knowldge.…”
Section: Introductionmentioning
confidence: 99%
“…( 16) we observe that the generalized Ricci scalar reduces to the standard Ricci scalar on shell. Therefore, the classical action ( 10) is on-shell equivalent to the Einstein-Hilbert action of classical GR, see [39,44,45] for recent detailed discussions. Since each component A μ ∈ R, the Einstein-Hilbert-Palatini action has an R 4 gauge invariance.…”
Section: Einstein-hilbert-palatini Actionmentioning
confidence: 99%
“…In fact, in [57], the authors introduce the so-called "relative bicomplex framework" and develop a geometric formulation of the covariant phase space methods with boundaries, which is used to endow the space of solutions with (pre)symplectic structures. These ideas are used to discuss formulations of Palatini gravity, General Relativity and Holst theories in the presence of boundaries [4][5][6]. On the other hand, a classic research topic has been the relationship between finite and infinite dimensional approximation to Classical Field Theories (see Sect.…”
Section: Introductionmentioning
confidence: 99%